REGULATORY UNCERTAINTY AS A CHALLENGE PROTECTION OF LEGITIMATE EXPECTATIONS FOREIGN INVESTORS: A LEGAL INVESTMENT PERSPECTIVE INDONESIA - Zulfikri Akramul Akbar; Arlansyah Harahap (Universitas Negeri Semarang, 2026)
Foreign direct investment (FDI) is a strategic instrument for Indonesia’s economic growth. However, the protection of foreign investors’ legitimate expectations namely, the reasonable expectation that the legal framework in place at the time of investment will remain stable and reliable has not yet been explicitly accommodated in Indonesia’s domestic investment laws. This study aims to examine the regulation and recognition of the legitimate expectations doctrine from the perspective of Indonesian investment law and to identify ways to optimize its protection in the face of regulatory uncertainty. The method used is normative legal research employing legislative, conceptual, and comparative approaches. The findings indicate that although Law No. 25 of 2007 on Investment and various BITs ratified by Indonesia implicitly recognize the principle of Fair and Equitable Treatment (FET), its implementation remains dependent on the subjective interpretation of government officials. Regulatory uncertainty stemming from overlapping central and local regulations, policy inconsistencies, and sudden regulatory changes including those in the implementation of the Job Creation Law significantly erode the legitimacy of foreign investors’ expectations. Optimizing protection requires vertical and horizontal regulatory harmonization, the implementation of Regulatory Impact Assessments (RIAs), institutional strengthening of the Investment Coordinating Board (BKPM), and the inclusion of more rigid stabilization and compensation clauses in